Autophagy inhibition improves the efficacy of curcumin/temozolomide combination therapy in glioblastomas. Issue 2 (28th March 2015) - Zanotto-Filho, Alfeu; Braganhol, Elizandra; Klafke, Karina; Figueiró, Fabrício; Terra, Sílvia Resende; Paludo, Francis Jackson; Morrone, Maurílio; Bristot, Ivi Juliana; Battastini, Ana Maria; Forcelini, Cassiano Mateus; Bishop, Alexander James Roy; Gelain, Daniel Pens; et al.
Abstract Glioblastoma is a devastating primary brain tumor resistant to conventional therapies. In this study, we tested the efficacy of combining temozolomide with curcumin, a phytochemical known to inhibit glioblastoma growth, and investigated the mechanisms involved. The data showed that synergy between curcumin and temozolomide was not achieved due to redundant mechanisms that lead to activating protective autophagy both in vitro and in vivo. Autophagy preceded apoptosis, and blocking this response with autophagy inhibitors (3-methyl-adenine, ATG7 siRNA and chloroquine) rendered cells susceptible to temozolomide and curcumin alone or combinations by increasing apoptosis. While curcumin inhibited STAT3, NFκB and PI3K/Akt to affect survival, temozolomide-induced autophagy relied on the DNA damage response and repair components ATM and MSH6, as well as p38 and JNK1/2. However, the most interesting observation was that both temozolomide and curcumin required ERK1/2 to induce autophagy. Blocking this ERK1/2-mediated temozolomide and curcumin induced autophagy with resveratrol, a blood–brain barrier permeable drug, improved temozolomide/curcumin efficacy in brain-implanted tumors. Overall, the data presented demonstrate that autophagy impairs the efficacy of temozolomide/curcumin, and inhibiting this phenomenon could provide novel opportunities to improve brain tumor treatment.